2019
DOI: 10.3390/molecules24213984
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin Has Potential for the Treatment of Escherichia coli-Induced Sepsis

Abstract: Isorhamnetin is a flavonoid that is abundant in the fruit of Hippophae rhamnoides L. It is widely studied for its ability to modulate inflammatory responses. In this study, we evaluated the potential of isorhamnetin to prevent gram-negative sepsis. We investigated its efficacy using an Escherichia coli-induced sepsis model. Our study reveals that isorhamnetin treatment significantly enhances survival and reduces proinflammatory cytokine levels in the serum and lung tissue of E. coli-infected mice. Further, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…7 Yang et al 49 proved that isorhamnetin treatment not only can significantly reduce the level of inflammatory cytokines in bronchoalveolar lavage fluid of mice, but also can protect mice from LPS-induced acute lung injury through inhibiting the activation of cyclooxygenase-2. Moreover, a recent study 50 revealed that isorhamnetin directly interacts with TLR4/MD-2 complex to prevent TLR4-mediated inflammatory cascade, which is consistent with the study by Kim et al 21 that isorhamnetin suppressed LPS induced inflammation in mouse microglia by inactivating NF-κB and blocking TLR4 pathway, reducing the expression of inflammatory factors such as TNF-α and IL-1β. In this study, we detected the expression of PRRs including TLR-2, TLR-4 and Dectin-1, and downstream inflammatory factors TNF-α and IL-1β in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…7 Yang et al 49 proved that isorhamnetin treatment not only can significantly reduce the level of inflammatory cytokines in bronchoalveolar lavage fluid of mice, but also can protect mice from LPS-induced acute lung injury through inhibiting the activation of cyclooxygenase-2. Moreover, a recent study 50 revealed that isorhamnetin directly interacts with TLR4/MD-2 complex to prevent TLR4-mediated inflammatory cascade, which is consistent with the study by Kim et al 21 that isorhamnetin suppressed LPS induced inflammation in mouse microglia by inactivating NF-κB and blocking TLR4 pathway, reducing the expression of inflammatory factors such as TNF-α and IL-1β. In this study, we detected the expression of PRRs including TLR-2, TLR-4 and Dectin-1, and downstream inflammatory factors TNF-α and IL-1β in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…This result is not significantly different compared to treatment group. As our knowledge, there was no other study describing the effect of Piper betle extract towards sepsis induced mice, however Chauhan et al, 2019, describe significant improvement of sepsis induced mice in isorhamnetin treated group [28].…”
Section: Figurementioning
confidence: 91%
“…Another study revealed that all treated group mice survived during observation period [28], however the survival rate of treated group mice was longer only 6 hours compared to positive control group. Several factors such as bioavailability, metabolism, and excretion may affect the effect of the extract administered orally.…”
Section: Figurementioning
confidence: 96%
“…Isorhamnetin, a avonoid abundant in the fruit of SB, showed a variety of anti-inammatory activities. [46][47][48][49] Besides ursolic acid and oleanolic acid, 45 two well-known anti-oxidant and anti-inammatory agents widely applied in cosmetics, casuarinin was also showed potent anti-inammatory property. 50 The detailed parameters of experiments including experimental models, dosage and possible mechanisms were listed in ESI Tab.…”
Section: Vitamin and Mineral Elementsmentioning
confidence: 99%